Integrasi Pasar Jangka Pendek Ayam Broiler di Indonesia - Ana Frasipa; Jojo Jojo (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
One of the fast-growing livestock subsectors is the poultry sector. This livestock subsector produces broiler chicken meat as a strategic commodity in addition to beef, milk, and eggs. The level of broiler chicken meat consumption is the highest order, followed by native chicken consumption, then beef. Broiler meat is a rapidly growing strategic commodity. This study uses ECM model analysis to determine the short-term market integration in broiler chickens—time series data on broiler chicken prices at the producer level between January 2015 and December 2020. This analysis's first step is testing broiler chicken meat producer price data stationarity in 28 provinces. Data that are not stationary will be heteroscedastic (have autocorrelation). In addition, time series data that are not stationary can also produce spurious regression, a condition in which two or more variables have a causality relationship, but there is no theory or logic underlying the direct causality relationship between two or more of these variables. According to the findings of this investigation, there is no complete integration. According to the study's findings, the weak flow of information in the market is suspected, so the information transmitted is not perfect. This shows that the broiler meat market in Indonesia leads to imperfect competition. The broiler's construction meat commodity market leads to oligopsony. Government intervention is required to establish broiler meat price control policies with the primary consideration of focusing on the price leader market that will be transmitted in harmony with other regions to make the broiler meat market structure more competitive.